'They shouldn't have to ask': Exploring the need for specialist mental health services for care-experienced and adopted children and their families. (July 2022) - Coulter, Stephen; Mooney, Suzanne; MacDonald, Mandi; Daly, Lesa
This article reports on a study conducted in two counties in the Republic of Ireland designed to elicit the views of fostering and adoption stakeholder groups on the mental health needs of the children, young people and families for whom they are responsible. Included in these groups are young people, adoptive parents, foster carers and professionals who manage and deliver mental health services or refer cases to them. Focus group methodology was employed to ascertain participants' views. The emerging data was analysed thematically and the key findings include: the need for a universal and integrated system offering mental health services; the importance of an attachment- and trauma-informed approach, incorporating a 'whole-family' perspective; the difficulties many families face in accessing timely and appropriate services with the associated risk of destabilising placements; the tension created by the balance between crisis responses and longer-term therapeutic support; poor levels of communication and collaboration between services; and a general aspiration to fashion a dedicated therapeutically focused service open to all foster and adoptive children and their families. Findings and recommendations are discussed in light of the existing models of good practice for providing integrated mental health services.